Misconceptions on the understanding of flying objects in fluids - Edy Wibowo; Naily Ulya; Whibatsu Helvantriyudo; Muhammad Maliki Azyumardi; Fata Hafiduddin; Mamat Rokhmat; Ismudiati Puri Handayani; Abrar Abrar; Nurwulan Fitriyanti; Sutisna Sutisna; Amira Saryati Ameruddin (Momentum: Physics Education Journal, 2023)
The concepts of floating, flying, and sinking object have been studied since junior high school. However, we still often find students' misconceptions regarding the concept, especially of flying objects, even at the university level. This work aims to propose a clarification of the concept of a flying object in the fluid to be correctly described the condition for the flying object. We used eggs, water, and salt solutions to demonstrate sinking, rising, and floating objects in the fluids. The results showed that when the density of the object is the same as the density of the fluid, the position of the object is still at the bottom of the fluid since it was not flying in the middle of the depth of the fluid. But the object does not touch the bottom of the container so that the object's height is zero. This is because the object has not had a driving force (Fd = 0) that pushes the object upward towards the surface of the fluid to float. When the density of the fluid slightly exceeds the density of the object, the object immediately moves upward to the fluid surface - floating phenomenon is started. The greater the difference between the density of the fluid and the density of the object, the faster the object moves towards the surface. The object cannot stay at any position between the bottom and the surface of the fluid. A stable position is reached when the object reaches the surface of the fluid to float. This work is expected to increase students' understanding of flying objects in fluids.